STEPS TOWARDS IMPLEMENTATION OF MODULAR HYBRID SYSTEM AT BAHRIA UNIVERSITY MEDICAL & DENTAL COLLEGE - Rehman, Rehana; Rubab, Zil e; Usmani, Ambreen; Rehan, Rabiya (Journal of Postgraduate Medical Institute, 2014)
This survey was carried out from November 2008 till Dec 2011 to establishproblem based learning (PBL) as part of hybrid modular curriculum at BahriaUniversity Medical & Dental College (BUMDC) Karachi. It describes all stepsundertaken to facilitate implementation of PBL system of education at BUMDC.During this period faculty was exposed to training workshops after whichthey were sequenced to prepare and present PBL in structured meetings andconduct them as facilitators. Faculty was exposed to 5 training workshops afterwhich a total of 12, 27, 29 and 28 PBLs in 2008, 2009, 2010 and 2011 wereprepared, presented and facilitated respectively. PBL system of educationwas implemented at BUMDC by stepwise measures which facilitated facultymembers to prepare and apply this strategy for learning of medical students.